Cervical subtotal discectomy prosthesis validated in non-human primate model: A novel artificial cervical disc replacement concept? - Liu, Yang; Wo, Jin; Zhu, Haoran; Huang, Zhonghai; Zhou, Pan; Yang, Jinpei; Zheng, Shuai; Zhou, Libing; Tan, Fengjin; Sun, Guodong; Li, Zhizhong (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: To evaluate the biological function of cervical subtotal discectomy prosthesis (CSDP) implantation in a non-human primate model. Methods: CSDP was tested for cytocompatibility and osseointegration capacity before implantation in non-human primates. Subsequently, the CSDP was improved based on three-dimensional CT measurements of the non-human primate cervical spine. Eight cynomolgus monkeys were selected to remove the intervertebral disc and lower endplate of the C5/6 segment to complete the model construction for CSDP implantation. In 18-month follow-up, physiological indices, radiology, and kinematics were assessed for the biological function estimation of CSDP in non-human primates, including biosafety, osseointegration, and biomechanics. Results: Co-cultured with the CSDP constituent titanium alloy (Ti6Al4V-AO), the mouse embryo osteoblast precursor cell (MC3T3-E1) obtained extended adhesion, remarkable viability status, and cell proliferation. After implantation in the mouse femur for 28 days, the surface of Ti6Al4V-AO was covered by a large amount of new cancellous bone, which further formed a connection with the femur cortical bone, and no toxicity of blood physiology or histopathology was detected. After completing implantation in primate models, no infections or osteolysis was observed, nor subsidence or displacement of the CSDP occurred in CT scans in 18-month follow-up. In particular, the interior of the cervical vertebra fixation structure was gradually filled with new trabecular bone, and the CSDP achieved fixation and bony fusion in vertebral body at 1 year post operation. Meanwhile, no signs of inflammation, spinal cord compression, adjacent segment degeneration, or force line changes were observed in the following MRI observations. Moreover, there were no pathological changes of the joint trajectory, joint motion range, stride length, and the stance phase ratio revealed in the kinematics analysis at 3, 6, 12, and 18 months after CSDP implantation. Conclusion: We designed a new cervical subtotal discectomy prosthesis and constructed an excellent non-human primate implantation model for the evaluation of subtotal disc replacement arthroplasty successfully. Furthermore, we demonstrated that CSDP had outstanding safety, osseointegration capacity, and biomechanical stability in a non-human primate model, which might be a new choice in the treatment of cervical disc diseases and potentially change the future outcome of degenerative cervical diseases.